Mathematizing Perceptions: Preservice Teachers’ Use of Mathematics to Investigate Their Relationship with the Community - Ksenija Simic-Muller (REDIMAT, 2015)
Preservice teachers often hold deficit views about the students they will teach and their communities. These limiting beliefs can result in lower expectations of and poor outcomes for the students, and need to be addressed in all areas of teacher education, including mathematics courses. In particular, mathematics content courses for preservice teachers offer numerous opportunities for investigating social justice issues and challenging preservice teachers’ beliefs. The assignment described in this manuscript provides an example of the work that can take place in mathematics content courses for preservice K-8 teachers. As part of the assignment, preservice teachers used mathematics to investigate negative perceptions that their campus community has of the surrounding neighborhood. They wrote reflections and created mathematical arguments about household income, poverty rates, educational attainment, crime, and diversity in the neighborhood. Through working on the assignment many preservice teachers began to question their stereotypes about the community. Because of the preservice teacher interest in the topic, and because some problematic beliefs were displayed in the reflections, there is a need for similar assignments in this and other courses, in order to help preservice teachers see the strengths of diverse communities, instead of just their shortcomings.